Study of microbial contamination ratios at al-Hilla Educational Hospital in Babylon Governorate /دراسة نسب التلوث الميكروبي في مستشفى الحلة التعليمي في محافظة بابل (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
During this study, the percentage of microbial contamination was calculated in the halls of Hilla Teaching Hospital during the period of five months from October 2016 to February 2017. We observed the percentage of pollution high in burns hall 10 contaminated swabs, the operating theaters 9 contaminated swabs, preterm infants and surgical resuscitation 6 contaminated swabs and 1 swab in the Nador Hall. In terms of internal rehabilitation and childbirth, screening of nursing staff and nutritionists,no microbial contamination was detected. The total number of polluted swabs was 32, followed by Staphylococcus aureus (24), 75%, Pseudomonas aeruginosa (5),15.6% and Escherichia coli (3), 9.4%. The isolates were tested for five (5) types of antimicrobial agents: Gentamicin, Amikacin, Meropenem, Ciprofloxacin, Cefotaxime, which showed heterozygous results for each bacteria and according to the type of antimicrobial agent